PWE-042 The relevance of the siewert classification in the era of multimodal therapy for adenocarcinoma of the gastro-oesophageal junction. (28th May 2012) - Noble, F; Bailey, I S; Kelly, J J; Byrne, J P; Underwood, T J
Abstract : Introduction: Since the early 1980s the Siewert classification has been used to plan treatment for tumours of the gastro-oesophageal junction. However, the relationship between tumour site and survival has not been conclusively demonstrated, with conflicting outcomes in the largest series, before the widespread application of neoadjuvant chemotherapy. The aim of this study was to evaluate whether there were differences in the biology and clinical characteristics of adenocarcinomas by Siewert type, in a contemporary cohort of patients, in whom the majority had received neoadjuvant chemotherapy. The relationship of the surgical approach and tumour site with patient survival was also assessed. Methods: A prospective database was reviewed for all patients who underwent resection for adenocarcinoma of the distal oesophagus and gastro-oesophageal junction from 2005 to 2011. In our unit, based on pre-operative assessment, distal oesophageal, type I and II tumours are treated as oesophageal cancer, with transthoracic procedures. Type III tumours are treated as gastric cancer with an abdominal approach. Classification systems used for analysis included TNM 7 for staging, Clavien-Dindo for grading complications and Siewert with final tumour site determined from the pathological specimen. Survival was estimated by Kaplan–Meier analysis excluding inpatient deaths (n=4) and R1 resections (n=42). Results: 216 patients underwent oesophagogastric resection: 133 for type I, 51 for type II and 33 for type III tumours. Median follow-up was 2.94 years. 62.5% of patients received neoadjuvant chemotherapy with no difference between groups. There were no significant differences in age, sex, pT stage, pN stage, pM stage, ASA, or inpatient complications between patients with adenocarcinoma based on their Siewert classification. Type I tumours were significantly associated with coexisting Barrett's metaplasia (presence of Barrett's: Type I 58.3%, Type II 21.6%, Type III 9.1%; pType II > Type I). Median overall survival was significantly shorter for more distal tumours (Type I: 4.96 years vs Type II: 3.3 years vs Type III: 2.64 years; p=0.04). The surgical approach did not influence survival for all tumour types and had no impact on the rate or severity of complications. Conclusion: This study demonstrates significant differences in the biological characteristics of adenocarcinomas of the gastro-oesophageal junction based on their anatomical topographical sub-classification. In the era of multimodal therapy overall survival is worse for tumours arising at or below the gastro-oesophageal junction compared with oesophageal tumours. Competing interests: None declared.